2019
DOI: 10.1111/ics.12505
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of Sanguisorba officinalis root extract on HYBID (KIAA1199)‐mediated hyaluronan degradation and skin wrinkling

Abstract: OBJECTIVES: Hyaluronan (HA), an important constituent of extracellular matrix in the skin, has many biological activities such as hydration that contributes to firmness and bounciness of the skin. We have reported that reduction in HA in the papillary dermis and over-expression of HYBID (HYaluronan Binding protein Involved in hyaluronan Depolymerization, alias KIAA1199 or CEMIP), a key molecule for HA degradation in skin fibroblasts, are implicated in facial skin wrinkling in Japanese and Caucasian women. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…However, no information was available for cosmetic agents that can modulate HYBID expression or activity. Therefore, we screened extracts from plants that are traditionally used as herbal or folk medicines in Asia and/or Europe, and discovered that Geranium thunbergii ( G. thunbergii ) extract and Sanguisorba officinalis ( S. officinalis ) root extract completely inhibit HA degradation in HYBID/HEK293 cells and normal human skin fibroblasts [59,60]. These extracts not only inhibited HA-degrading activity of HYBID but also downregulated the HYBID gene expression, leading to production of high-molecular-weight HA [59,60].…”
Section: Screening Of Agents That Inhibit the Expression And Activmentioning
confidence: 99%
See 3 more Smart Citations
“…However, no information was available for cosmetic agents that can modulate HYBID expression or activity. Therefore, we screened extracts from plants that are traditionally used as herbal or folk medicines in Asia and/or Europe, and discovered that Geranium thunbergii ( G. thunbergii ) extract and Sanguisorba officinalis ( S. officinalis ) root extract completely inhibit HA degradation in HYBID/HEK293 cells and normal human skin fibroblasts [59,60]. These extracts not only inhibited HA-degrading activity of HYBID but also downregulated the HYBID gene expression, leading to production of high-molecular-weight HA [59,60].…”
Section: Screening Of Agents That Inhibit the Expression And Activmentioning
confidence: 99%
“…Therefore, we screened extracts from plants that are traditionally used as herbal or folk medicines in Asia and/or Europe, and discovered that Geranium thunbergii ( G. thunbergii ) extract and Sanguisorba officinalis ( S. officinalis ) root extract completely inhibit HA degradation in HYBID/HEK293 cells and normal human skin fibroblasts [59,60]. These extracts not only inhibited HA-degrading activity of HYBID but also downregulated the HYBID gene expression, leading to production of high-molecular-weight HA [59,60]. Small-scale clinical trials of G. thunbergii extract and S. officinalis root extract as an anti-wrinkle agent were performed with Japanese females, who topically applied the test formulation containing each extract on one side of the outer eye-corner and the placebo formulation on the other side twice daily for eight weeks.…”
Section: Screening Of Agents That Inhibit the Expression And Activmentioning
confidence: 99%
See 2 more Smart Citations
“…Several in vivo and in vitro studies have demonstrated that ZY-I increases the contents of collagen and elastic fibers in a dose-dependent manner and also inhibits the production of the collagen-degrading enzyme MMP-3 in the skin, thereby demonstrating an anti-wrinkle effect (Kim et al, 2008;Yun et al, 2019). In a randomized double-blind placebo experiment conducted with 21 Japanese women, it was observed that at the cellular level, it was the S. officinalis root extract, rather than ziyuglycoside-I, that inhibited the hyaluronic acid degradation and consequently exerted the anti-wrinkle effect (Yoshida et al, 2018). Interestingly, when the chemical constituents of the root, stem, and leaf extracts of S. minor were analyzed, it was revealed that the content of polyphenols was significantly higher in the stem and leaf extracts compared to that in the root extracts.…”
Section: Antioxidant Activitymentioning
confidence: 99%